POLA BAKTERI PADA ULKUS DIABETIKUM GRADE TIGA DI KLINIK LUKA DIABETES KOTA MAKASSAR - Alifia Ayu Delima (Universitas Pahlawan Tuanku Tambusai, 2022)
Diabetes Mellitus is a global health problem and is one of the top 10 causes of death globally. One of the main complications of diabetes mellitus is diabetic ulcers. In Indonesia, the incidence of diabetic ulcers is reported to be around 12% and the risk of diabetic ulcers is around 55.4%. Incidence Infection is very common (40-80%) so it is a major cause of morbidity and mortality. Microbes in diabetic foot wounds can be monomicrobial and polymicrobial. This study aims to determine the bacterial pattern in diabetic ulcers. This study was conducted in vitro on isolates of third grade diabetic ulcers from 15 samples. Antimicrobial tests were carried out by inoculation on PCA (Plate Count Agar) and MSA (Mannitol Salt Agar) media. The results showed that the bacterial patterns seen were Staphylococcus haemolyticus, Staphylococcus aureus, Proteus Mirabilis, and Acinetobacter baumanii. In conclusion, the most common bacteria found in this study was Proteus mirabilis. Keywords: Diabetic ulcer, diabetes mellitus, bacterial pattern